1997
DOI: 10.1111/j.1432-2277.1997.tb00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Two grams daily of oral acyclovir reduces the incidence of cytomegalovirus disease in CMV-seropositive liver transplant recipients

Abstract: Our objective in this study was to determine the efficacy of 2 grams a day of oral acyclovir administered for 16 weeks after transplantation for the prevention of cytomegalovirus (CMV) infection and disease in CMV-seropositive liver transplant recipients. Seventythree adult liver transplant recipients, seropositive for CMV, were I randomized to receive either 2 grams a day of oral acyclovir for 16 weeks after transplantation or no prophylaxis. The incidence of CMV disease was significantly lower in the acyclov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Similarly, high-dose acyclovir with targeted intravenous ganciclovir administration during antilymphocyte antibody therapy appears to be an effective strategy against CMV reactivation in those receiving either a kidney or kidney-pancreas allograft (35,417). Results of similar studies done on liver transplant recipients have been disappointing (284,423,497), although one study suggested a beneficial effect with 2 g of oral acyclovir a day taken by CMV-seropositive liver transplant recipients for 16 weeks (145). While acyclovir is not particularly active against CMV in vitro, it is possible that the achievable cellular levels will inhibit the small amounts of replicating virus that are present as it emerges from latency.…”
Section: Specific Antiviral Prophylaxismentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, high-dose acyclovir with targeted intravenous ganciclovir administration during antilymphocyte antibody therapy appears to be an effective strategy against CMV reactivation in those receiving either a kidney or kidney-pancreas allograft (35,417). Results of similar studies done on liver transplant recipients have been disappointing (284,423,497), although one study suggested a beneficial effect with 2 g of oral acyclovir a day taken by CMV-seropositive liver transplant recipients for 16 weeks (145). While acyclovir is not particularly active against CMV in vitro, it is possible that the achievable cellular levels will inhibit the small amounts of replicating virus that are present as it emerges from latency.…”
Section: Specific Antiviral Prophylaxismentioning
confidence: 93%
“…Current prophylactic approaches vary widely among different transplant programs (5,8,18,26,72,104,105,143,145,172,232,236,273,284,299,319,382,396,423,497) (Table 5). Reasons for the discrepancies reflect the absence of large, multicenter, randomized trials evaluating the efficacy of countless preventive strategies.…”
Section: Specific Antiviral Prophylaxismentioning
confidence: 99%
“…Conceptual presentation of the risk of late-onset CMV disease with antiviral prophylaxis in organ transplant recipients; data compiled from [1][2][3][4][5][6][7]19,20,35,36]. The risk of late-onset CMV is low (0-5%) if a relatively less potent antiviral agent (acyclovir) is employed for a prolonged period [5,6] or if a potent drug (valganciclovir) is used for a short period (0%) as in preemptive therapy [19,20,22].…”
Section: Lowmentioning
confidence: 99%
“…17 The availability of effective therapy [18][19][20] has reduced this figure significantly among renal-transplant recipients, 8,21 but the increased morbidity and overall costs of transplantation associated with CMV persist. 10,22 High-dose oral acyclovir is well tolerated, but prophylactic use of acyclovir has not gained wide acceptance 9 despite the fact that it reduces the risk of CMV disease among recipients of renal [23][24][25] and other solid-organ [26][27][28] transplants. The limited efficacy of acyclovir may be a result of its low oral bioavailability and the low in vitro sensitivity of CMV to the drug.…”
Section: Introductionmentioning
confidence: 99%